(untitled) (Biological Sciences - PJSIR, 1995)
Pot and field experiments wereconducted to assess the response of maize (Zea mays L.) to Zinc application and the effect of Phosphorus on Zinc distribution in plants. It was observed that maize responded significantly (P <0.01) _ to Zn application and showed positive P x Zn interaction for growth as well as grain yield depending on soilZn level and maize variety. Application of Zn increased Zn concentration in all plant parts including grain while application of P tended to decrease Zn concentration in plants. The results suggest that only small amount of Zn should be applied to soils containing marginal soil Zn in order to obtain better maize growth and yield.